Public Versus Private Protection Against Crime : The Case of Somali Piracy - Do, Quy-Toan; Ma, Lin; Ruiz, Claudia (World Bank, Washington, DC, 2016)
This paper analyzes the rise and demise of piracy off the coast of Somalia to highlight the interplay between public and private crime protection measures. Using unique data on attacks, hijacks, and ransoms, the authors estimate a structural model of Somali piracy to calculate the elasticity of crime with respect to two forms of protection: the publicly-provided deployment of international navies in the Western Indian Ocean and the private provision of maritime security contractors on board vessels. They assess both positive and negative spillovers associated with private security. Their findings have implications for the optimal composition of protective measures and the regulation of the market for private security.